Complexation Engineering of Electron Transport Layers for High‐Performance Perovskite Solar Cells. Issue 8 (1st May 2022) - Lin, Zhichao; Zhang, Wenqi; Cai, Qingbin; Xu, Xiangning; Dong, Hongye; Mu, Cheng; Zhang, Jian-Ping
Abstract : For high‐performance perovskite solar cells (PSCs), transition metal complexes as modifiers are used to optimize the energy‐level alignment of the SnO2 electron transport layer (ETL), reduce the defects at the ETL/perovskite interface, and improve the crystallinity of the perovskite layer. Herein, it is shown that application of [Ni(NH3 )6 ]F2 or [Co(NH3 )6 ]F2 complexes yields a substantially improved open‐circuit voltage and fill factor, and thereby photoelectric conversion efficiency (PCE). The optimum PCEs of the [Ni(NH3 )6 ]F2 ‐ or [Co(NH3 )6 ]F2 ‐treated PSCs reach 22.58% and 22.47%, respectively, which are much higher than that of the unmodified PSC (20.21%). This study provides a direction for improving the performance of a planar PSC using a complex‐modified ETL. Abstract : Divalent transition metal complexes [Ni(NH3 )6 ]F2 or [Co(NH3 )6 ]F2 optimize the energy‐level arrangement of an SnO2 electron transport layer (ETL), passivate the defects of the ETL/perovskite interface, and improve the crystallinity of the perovskite layer.